259 Randomised controlled trial of a text message alcohol intervention following an injury admission. (1st September 2016) - Sharpe, Sarah; Kool, Bridget; Whittaker, Robyn; Lee, Arier; Reid, Papaarangi; Civil, Ian; Smith, Gordon S; Walker, Matthew; Thornton, Vanessa; Ameratunga, Shanthi
Abstract : Background: Despite known benefits, brief interventions (BIs) for problem drinking are often not implemented in trauma care wards due to resource constraints. We evaluated a mobile phone text message intervention (YourCall) designed to overcome this challenge. Methods: Of 1564 potentially eligible injured patients aged 16–69 years recruited from the three trauma admitting public hospitals in Auckland and screened using the Alcohol Use Disorders Identification Test (AUDIT), 598 were identified as moderate risk drinkers and enrolled in a parallel, single-blind RCT. The intervention group received 16 text messages incorporating BI principles in the four weeks after hospital discharge. Controls received one text message acknowledging participation in the study. Primary outcomes comprised differences in hazardous alcohol use (AUDIT-C) between the intervention and control groups at 3, 6 and 12 months following the injury. Data were analysed using a mixed-effects model for repeated measures. Results: Baseline features were similar in both groups (71% males; mean age 34 years; 21% Māori, 62% European; mean AUDIT-C 6.8). Significant reductions in hazardous alcohol use during follow-up were observed in both groups. A small but significantly lower risk of hazardous drinking was evident in the intervention compared with control group (least square means difference: −0.322; 95% CI: −0.636, −0.008). This effect was maintained across the 12-months of follow-up and similar among Māori and non-Māori (interaction p = 0.257). Conclusions: The effect of the Your Call intervention was similar to most standard BIs despite its modest intensity and the restriction of this trial to moderate risk participants only. Text interventions are scalable low cost approaches that can overcome barriers and inequities in implementing BIs in trauma care settings. The expanding cell phone coverage makes this modality particularly salient in economically disadvantaged groups and low- and middle-income countries.